Burundi : Staff Report for the 2003 Article IV Consultation and Request for Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). (IMF Staff Country Reports; Country Report ;, 2004)
Burundi has made much progress since the signing of the Arusha peace and reconciliation agreement. The handling of the economy has been highly competent considering the inordinate difficulties faced by Burundi in recent years. The bank of the Republic of Burundi has made progress in the implementation of monetary policies and in the conduct of bank supervision. Progress in implementing structural reforms has been satisfactory overall. Burundi continues to face unsustainably heavy debt-service obligations. The government is gradually rebuilding its administrative capacity.